THE INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON CUSTOMER SATISFACTION OF SAMSUNG SMARTPHONE USERS IN MANADO - Sekeon, Tria; Pandowo, Merinda H. Ch.; Saerang, Regina T. (Universitas Sam Ratulangi, 2024)
This study aims to determine the influence of product quality and brand image on customer satisfaction of Samsung smartphone users in Mando. The sample used 100 Samsung smartphone users. The sampling technique in this study uses a criteria sampling method. Data were collected using a questionnaire with a Likert scale. The analysis method used in this research is a multiple linear regression analysis method with SPSS 25 apps. The result based on (the t-test) shows that product quality and brand image have a significant influence on customer satisfaction with a significance value of .000 < .05 for product quality and .031 < .05 for brand image. The F-test result obtained a significance value of .000 < (.05). This concluded that simultaneously, the variables Product Quality (X1) and Brand Image (X2) have a significant influence on Customer Satisfaction (Y). Keywords: Product Quality, Brand Image, Customer Satisfaction